Study on corrosion durability of ferrocement - Mansur, Mohammad A. (American Concrete Institute, 2008)
An electrochemical-based accelerated corrosion technique has been employed to study the corrosion durability of ferrocement. Variables considered include cover thickness; composition of the matrix in terms of water-cement ratio (w/c), sand-cement ratio (s/c), and contents of mineral and chemical admixtures; and use of stainless steel wire mesh. After suitable exposure, maximum crack width, percentage of steel loss, and reduction in flexural strength served as the bases for assessing the relative performance of various means considered. Test results indicate that the addition of mineral admixtures, application of a suitable surface coating, and the use of deeper concrete cover provide excellent protection against reinforcement corrosion. Employment of stainless steel as reinforcement and the use of so-called corrosion inhibitor or a low w/c in the matrix also slows down the corrosion process, but is not as effective as others. Based on test results, a hybrid protection system combining three lines of defense is suggested for enhanced durability of ferrocement.